2021
DOI: 10.3390/cells10112810
|View full text |Cite
|
Sign up to set email alerts
|

An Inducible System for Silencing Establishment Reveals a Stepwise Mechanism in Which Anchoring at the Nuclear Periphery Precedes Heterochromatin Formation

Abstract: In eukaryotic cells, silent chromatin is mainly found at the nuclear periphery forming subnuclear compartments that favor silencing establishment. Here, we set up an inducible system to monitor silencing establishment at an ectopic locus in relation with its subnuclear localization in budding yeast. We previously showed that introducing LacI bound lacO arrays in proximity to gene flanked by HML silencers favors the recruitment of the yeast silencing complex SIR at this locus, leading to its silencing and ancho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…These observations further support that a long (>9 kb) inactive region from a different organism but with a similar GC content than S. cerevisiae can be a contact hotspot for the 2µ plasmid. It has been shown that a high level of LacI binding results in nucleosome eviction (Loïodice et al, 2021). The observation that specific contact is lost when the LacI protein is attached to the region suggests that the resulting large nucleosome-free region could be responsible for the detachment of the 2µ plasmid.…”
Section: µ Plasmid Tether To Exogenous Artificial Inactive Chromatinmentioning
confidence: 99%
“…These observations further support that a long (>9 kb) inactive region from a different organism but with a similar GC content than S. cerevisiae can be a contact hotspot for the 2µ plasmid. It has been shown that a high level of LacI binding results in nucleosome eviction (Loïodice et al, 2021). The observation that specific contact is lost when the LacI protein is attached to the region suggests that the resulting large nucleosome-free region could be responsible for the detachment of the 2µ plasmid.…”
Section: µ Plasmid Tether To Exogenous Artificial Inactive Chromatinmentioning
confidence: 99%
“…First, in Neurospora , a synthetic tetO operator array was shown to activate RIP by the heterochromatin-related pathway, suggesting that such a construct could initiate transcriptional silencing de novo [29]. Second, in budding yeast, the association of such operator arrays with their corresponding repressor proteins (LacI or TetR) was also shown to induce transcriptional silencing of a nearby reporter [30,31]. This process started with phosphorylation and concomitant depletion of histone H2A, suggesting that the tight binding of repressor proteins led to chromatin stress and nucleosome loss; and it did so by a mechanism independent of DNA replication [30].…”
Section: Introductionmentioning
confidence: 99%
“…Second, in budding yeast, the association of such operator arrays with their corresponding repressor proteins (LacI or TetR) was also shown to induce transcriptional silencing of a nearby reporter [30,31]. This process started with phosphorylation and concomitant depletion of histone H2A, suggesting that the tight binding of repressor proteins led to chromatin stress and nucleosome loss; and it did so by a mechanism independent of DNA replication [30]. The perturbed array was directed to the perinuclear compartment, where it became gradually occupied by Silent Information Regulator (SIR) proteins, the critical effectors of transcriptional silencing in budding yeast [30].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations